STRATIGRAPHIC AND GEOGRAPHIC DISTRIBUTION OF THE ORDOVICIAN CORAL FAMILY AGETOLITIDAE - Serezhnikova E.A. (My University, 2003)
Stratigraphic and geographic distribution of corals of the family Agetolitidae Kim is analyzed. The family is a unique group bearing characters of both tabulatomorphic and rugose corals.
Keywords: Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская